Growth Performance of Nile tilapia Immersed in 17α-methyltestosterone and rElGH, and Fed a Diet Enriched with rElGH - Muhammad Safir; Alimuddin Alimuddin; Mia Setiawati; Muhammad Zairin Junior; Muhammad Agus Suprayudi (Journal Omni-Akuatika, 2017)
The aim of the present study was to investigate the growth performance of Nile tilapia immersed in 17α-methyltestosterone (MT) and recombinant giant grouper growth hormone (rElGH), and fed a rElGH-enriched diet. A total of 200 tilapia larvae aged 10 days and 14 days post hatching was immersed in 1 liter of 30 g/L saline water for 3 minutes, then in freshwater containing either MT, MT+rElGH, or rElGH for 4 hours. The MT dose was 2.0 mg/L and rElGH was 2.5 mg/L. As control was treatment without MT and rElGH. Fish were maintained in 250-L aquariums for 6 weeks and then moved to net cages for 8 weeks of rearing. The rElGH-enriched diet was fed to the 6-week-old fish for a month, and then fed a non-enriched diet. Each treatment was triplicates. The result showed that the daily growth rate (DGR), biomass gain (BM), survival (SR) and feed (artemia nauplii) consumption during maintenance in the aquariums in the rElGH and MT+rElGH treatments were higher (P<0.05) than in the control. The higher DGR and BM at net cage rearing and lower feed conversion ratio (P<0.05) were also found in MT and MT+rElGH treatments. None of the treatments showed any difference in survival (P>0.05). Profits estimation in the MT and MT+rElGH treatments were 63.38% and 57.91% higher than the control. The present study concluded that higher Nile tilapia farming performance could be obtanied by MT immersion in the larval phase and feeding juvenile on the rElGH-enriched diet.